DESCRIPTION ABSORPTION DOSE OF CHILDREN X-RAY THORAX IN RADIOLOGY INSTALATION DR ARIO WIRAWAN SALATIGA - Siti Daryati; Rini Indrati; Novriyati Wahyu Illahi (Poltekkes Kemenkes Semarang, 2019)
Backgroud:One of the most frequent radiological examinations is the child's thorax. Children have high organ sensitivity to radiation because their organs are not yet mature. The purpose of this study was to determine the radiation dose received by children during the examination of the thorax at Instalasi Radiology Rumah Sakit Paru dr. Ario Wirawan Salatiga.Methods:This research is a quantitative research with the observational approach. Research done by mounting the chip TLD in the body of the child, samples used is 10 pediatric patients 1-15 years. Then the radiation dose compared to the dose limit values recommended by UNSCEAR, for children aged 1-4 years the safe dose limit of 0.03 mGy, children 5-9 years 0.04 mGy, and for children 10- 15 years 0.05 mGy.Results: Results of measurement of radiation absorbed dose for children 1-4 years old highest by 0.116 mGy and the lowest was 0.044 mGy. For children 5-9 years the highest absorbed dose of 0.130 mGy and the lowest was 0.036 mGy, while for children 10-15 years acceptable dose of 0.043 mGy.Conclusion:Results of measurement of radiation dose in Instalasi Radiology Rumah Sakit Paru dr. Ario Wirawan Salatiga is then compared with the recommendations issued by UNSCEAR (2000) in children 1-4 years absorbed dose received exceeds the allowed limit (0.03 mGy) for receiving the average absorbed a dose of 0.085 mGy. In children 5-9 years absorbed dose received also exceeded the allowed limit (0.04 mGy) for receiving absorbed dose by an average of 0.092 mGy, while the absorbed dose in children 10-15 years who received still within safe limits (0.05 mGy) for receiving a dose of 0.043 mGy.